INTELLECTUAL DIVERSITY IN POSTMODERN REALITY - Ravochkin, Nikita; Porhachev, Vasiliy; Shchennikov , Vladimir; Petrov , Mikhail; Shtumpf, Svetlana; Rakhinsky, Dmitry (Revista Inclusiones, 2020)
The present article examines intellectual diversity rapidly developing and diversifying in the postmodern world condition. The essence of intellectual revolutions and their positive and negative consequences are demonstrated. The transformation of the image of intellectuals is presented. The authors define ideas as the basis for the practical realization of social transformations. The currently relevant specifics of formation and accumulation of the arsenal of ideas by intellectual networks are demonstrated. The conditions for the acceleration of intellectual and social dynamics are examined. The way in which the reconsideration of the problem of “the Other” directly influences the durability of intellectual networks’ functioning and allows generating new ideas is described. The characteristic features of the ideological determination of various social transformations are identified.